2019
DOI: 10.20546/ijcmas.2019.801.224
|View full text |Cite
|
Sign up to set email alerts
|

Mega–Environment Concept in Agriculture: A Review

Abstract: Greater emphasis on future constraints to agricultural production is motivated by the projections of environmental change. The speed of population, change in climate and environmental has pressurized the crop community to understand the importance of those stresses which may result in the significant declines in yield. Advances in data availability, advance information technology, and new and improved methods to target genotypes to environments have benefited the crop improvement practices. No methodology is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To study the spatial variation in production, the wheatgrowing regions of India are divided into spring wheat environments (SWEs) based on the mega-environment concept (Chowdhury et al, 2019). For this purpose, we divide the wheat-growing regions of India into five SWEs (Fig.…”
Section: Country-scale Simulationsmentioning
confidence: 99%
“…To study the spatial variation in production, the wheatgrowing regions of India are divided into spring wheat environments (SWEs) based on the mega-environment concept (Chowdhury et al, 2019). For this purpose, we divide the wheat-growing regions of India into five SWEs (Fig.…”
Section: Country-scale Simulationsmentioning
confidence: 99%
“…Silva et al [10] reported that mega-environment trials could lead to complex GEIs and obtained information about the relationship between trial environments. Information obtained from mega-environment trials was very helpful for plant breeders in managing GEIs and extracting them into the same agro-climatic concept [11]. According to Zdziarski et al [12], mega-environment trial provides information on specifc adapted lines based on regional targets and regional climate.…”
Section: Introductionmentioning
confidence: 99%
“…Modern agriculture has been continuously compelled to advance and to make use of sustainable technologies. Such technologies include genetic breeding tools, efficient-release fertilizers, soil management strategies, intelligent use of water and agrochemicals, internet of things, crop and weather monitoring, nanotechnology and integrated techniques of farm administration among others (Ali et al, 2018;Chowdhury et al, 2019;Leakey et al, 2019;Lowenberg-DeBoer & Erickson 2019;Pandey et al, 2019;Saiz-Rubio & Rovira-Má s, 2020;Singh & Singh, 2020;Devlet, 2021).…”
Section: Introductionmentioning
confidence: 99%